Aspects on advanced procedures during endoscopic retrograde cholangiopancreatography (ERCP) for complex hepatobiliary disorders - Lubbe, Jeanne Adele (Stellenbosch : Stellenbosch University, 2021)
Background: The rapid development in endoscopic technology and associated skills has led to an increase in more advanced procedures being performed during endoscopic retrograde cholangiopancreatography (ERCP). Knowledge is limited regarding clinical value, integration, and outcomes for single operator cholangiopancreatoscopy (SOCP) and endoscopic intervention in the different Bismuth-Corlette (B-C) locations in the hepatic hilum. Objectives: To determine the clinical value of SOCP in the diagnosis and treatment of complex hepatobiliary and pancreatic disease. To describe the nationwide integration of SOCP and the extent to which adverse events are influenced when SOCP is added to ERCP. To compare adverse events and reintervention rates after endoscopic stenting for malignant obstruction in the distal and hilar locations of the biliary tree. To compare outcomes after endoscopic transpapillary (ETP) and percutaneous transhepatic (PTH) stenting in the palliation of malignant hilar obstruction (MHO). Methods: In study I all SOCP procedures performed between March 2007-December 2014 at a tertiary highvolume endoscopy unit were separately graded according to a predefined 4-graded scale estimating therapeutic value and diagnostic yield. Study II was a nationwide case-control study nested within the cohort of ERCP procedures, with- or without SOCP, and registered in the Swedish Registry for Gallstone Surgery and ERCP (GallRiks) between 2007-2012. To assess risk factors for adverse events, multivariate logistic regression was performed, and odds ratios (OR) calculated. The GallRiks registry was also utilised in study III where all patients undergoing endoscopic stenting for malignant biliary obstruction between 2010-2017 (based on International Classification of Diseases (ICD) coding), were included. Kaplan-Meier analysis was employed to calculate stent patency and Cox proportional hazard models to calculate the risk for recurrent biliary obstruction after single metal stent placement. To compare ETP and PTH drainage approaches, a retrospective deconstructed analysis of palliative stenting procedures for MHO at two specialised referral centres over a 5-year period was performed. Within-group analyses were performed to explore outcomes for different B-C types and Kaplan-Meier and restricted mean survival time analyses were performed to calculate and compare duration of therapeutic success. Results: In 365 SOCP procedures, SOCP was found be of pivotal importance in 19% of patients, of great clinical significance in 44%, and did not affect clinical decision-making or alter clinical course in 37% of patients. In study II a learning curve was observed after first introduction of 408 SOCP procedures, and postprocedural adverse events (19.1% vs. 14.0%), pancreatitis (7.4% vs. 3.9%) and cholangitis (4.4% vs. 2.7%) were more prevalent when SOCP was added to ERCP. After multivariate analysis, the risk for postprocedural adverse events remained (OR 1.35, 95% CI [1.04 - 1.74]). In 4623 ERCP procedures performed for stenting of malignant strictures (1364 hilar), adverse events and 6-month reintervention rates were increased after hilar stenting compared to distal stenting (17.2% vs. 12.0%, 73.4% vs. 55.9%). On multivariate analysis the risk for reintervention was three times higher after single metal stent placement in the hilum compared to the distal biliary tree (HR 3.47, 95% CI [2.01-6.00], p<0.001). In 293 patients undergoing palliative stenting for MHO (52.2% ETP, 47.8% PTH), access and bridging success in the ETP and PTH groups were 83.5% vs. 97.2% and 90.2% vs. 84.5%, respectively. Technical and therapeutic success were equivalent between the two groups, but duration of therapeutic success was longer after ETP drainage, with a 3-month gain in duration of therapeutic success after adjustment for B-C type (95% CI [26-160], p=0.006). Cholangitis rates were equivalent (21.4% vs. 24.7%), while pancreatitis was more common in the ETP group and deaths more common in the PTH group. Conclusions: When added to ERCP, SOCP contributes significant clinical value in 64% of cases. However, there is an increased risk of intra- and postprocedural adverse events which, together with a learning curve, suggests that it should likely be performed in specialised high-volume centres. Regarding endoscopic intervention for MHO, stenting in the hepatic hilum compared to the distal biliary tree is associated with more adverse events and decreased stent patency. When comparing palliative ETP with PTH stenting for MHO, both approaches have similar technical and therapeutic success, with ETP drainage being more durable. Future studies should explore the complimentary role of both approaches in specific B-C types.